Model Selection, Forecasting and Monthly Seasonality of Hotel Nights in Denmark - Nils Karl Sørensen (European Regional Science Association (ERSA), 2004)
Foreigners' demand for hotel nights in Denmark by nationality are examined using monthly time series covering 30years, and divided into 11 nationalities. Special attention is given to the role of seasonality. Three univariate seasonal presentations of non-stationary data with different characteristics are considered, a stochastic, deterministic, and an error correction mechanism (ECM) approach taking into account economic as well as climatic variables. Based on a presentation of different measures to evaluate the forecasting performance a model selection is under taken. It is found that the single variable presentations in most cases are superior to the ECM. On the other hand the ECM presentation provides a more detailed description of the evolution of inbound tourism. In many cases it is found that the climatic indicators have significant influence on tourism. With regard to the single variable models it is found that seasonality in general is of stochastic nature, but the deterministic presentation is in many cases superior in forecasting performance. Theme: Tourism, regional econometric modelling Key words: Tourism, seasonality, fore casting, climatic variables. JEL Classification: C32.
Keywords: C32; 330; Tourism; seasonality; fore casting; climatic variables